Loss of Function of Scavenger Receptor SCAV-5 Protects C. elegans Against Pathogenic Bacteria - Luo, Aixiao; Jing, Huiru; Yuan, Lei; Wang, Yanzhe; Xiao, Hui; Zheng, Qian (Frontiers in Cellular and Infection Microbiology, 2021)
Scavenger receptors play a critical role in innate immunity by acting as the pattern-recognition receptors. There are six class B scavenger receptors homologs in C. elegans. However, it remains unclear whether they are required for host defense against bacterial pathogens. Here, we show that, of the six SCAV proteins, only loss of function scav-5 protect C. elegans against pathogenic bacteria S. typhimurium SL1344 and P. aeruginosa PA14 by different mechanism. scav-5 mutants are resistant to S. typhimurium SL1344 due to dietary restriction. While scav-5 acts upstream of or in parallel to tir-1 in conserved PMK-1 p38 MAPK pathway to upregulate the innate immune response to defend worms against P. aeruginosa PA14. This is the first demonstration of a role for SCAV-5 in host defense against pathogenic bacteria. Our results provide an important basis for further elucidating the underlying molecular mechanism by which scav-5 regulates innate immune responses.